Increase in the risk of type 2 diabetes during lockdown for the COVID19 pandemic in India: A cohort analysis (2020)
Lockdown due to the Coronavirus disease 2019 (COVID 19) pandemic may cause weight gain and enhance the risk of type 2 diabetes mellitus (T2DM). We aimed to determine this risk in apparently nondiabetic individuals. Material methods: Baseline demographic and clinical data from 100 apparently non-diabetic household members (related or unrelated) of patients with type 2 diabetes mellitus were collected until 49 days of lockdown and analyzed using the XL-STAT statistical software. A two-pronged analytical strategy was employed. First, the metabolic risk profile related to age, sex, weight, family history, and exercise pattern was analyzed. This was followed by an assessment of the risk of developing type 2 diabetes using an established risk assessment engine. Results: There was a trend towards weight gain seen in 40% of the cohort, with 16% of the population experiencing a 2.1e5 kg weight increment. When all the risk parameters were analyzed together using the ADA risk engine, there was an increase in the ADA diabetes risk score in 7% of the population, with 6.66% in the high-risk group. There was a further increase in weight among 3% of the population who were already obese at baseline. Conclusion: We show an increased risk of T2MD consequent to weight gain during 49 days of lockdown in India